Solid lithium electrolyte-Li4Ti5O12 composites as anodes of lithium-ion batteries showing high-rate performance - Sha, Y.; Yuan, T.; Zhao, B.; Cai, R.; Wang, H.; Shao, Zongping (Elsevier SA, 2013)
A new concept lithium-ion conducting lithium lanthanum titanate solid electrolyte and Li4Ti5O12composite is proposed as efficient anode of lithium-ion batteries with outstanding rate performance,which can be facilely prepared by one-pot combustion technique. The as-synthesized composites are in micrometer size with dense nature which effectively reduces the electrode-liquid electrolyte interface area, thus decreasing irreversible capacity during the first chargeedischarge cycle and prolonging cycling stability. However, the composites are rich in lithium lanthanum titanate and Li4Ti5O12 dual phase boundaries due to intimate nanoscale mixing of the two phases. The apparent lithium-ion conductivity of the composite electrode gets significantly improved as compared to pristine Li4Ti5O12 due to the incorporation of lithium lanthanum titanate phase, a high lithium ionic conductor. As a result, the assynthesized composites show a high capacity of 113.5 mA h g1 even at a discharge rate of 40 C, more than 200% that of a pristine Li4Ti5O12. The concept is general, which may also be applicable to other electrode materials, and it thus introduces a new way for the development of high rate-performance electrodes for lithium-ion batteries.